20-HETE Signals Through G-Protein–Coupled Receptor GPR75 (Gq) to Affect Vascular Function and Trigger Hypertension. Issue 11 (26th May 2017) - Garcia, Victor; Gilani, Ankit; Shkolnik, Brian; Pandey, Varunkumar; Zhang, Frank Fan; Dakarapu, Rambabu; Gandham, Shyam K.; Reddy, N. Rami; Graves, Joan P.; Gruzdev, Artiom; Zeldin, Darryl C.; Capdevila, Jorge H.; et al.
Abstract : Rationale: : 20-Hydroxyeicosatetraenoic acid (20-HETE), one of the principle cytochrome P450 eicosanoids, is a potent vasoactive lipid whose vascular effects include stimulation of smooth muscle contractility, migration, and proliferation, as well as endothelial cell dysfunction and inflammation. Increased levels of 20-HETE in experimental animals and in humans are associated with hypertension, stroke, myocardial infarction, and vascular diseases. Objective: : To date, a receptor/binding site for 20-HETE has been implicated based on the use of specific agonists and antagonists. The present study was undertaken to identify a receptor to which 20-HETE binds and through which it activates a signaling cascade that culminates in many of the functional outcomes attributed to 20-HETE in vitro and in vivo. Methods and Results: : Using crosslinking analogs, click chemistry, binding assays, and functional assays, we identified G-protein receptor 75 (GPR75), currently an orphan G-protein–coupled receptor (GPCR), as a specific target of 20-HETE. In cultured human endothelial cells, 20-HETE binding to GPR75 stimulated Gαq/11 protein dissociation and increased inositol phosphate accumulation and GPCR-kinase interacting protein-1-GPR75 binding, which further facilitated the c-Src–mediated transactivation of epidermal growth factor receptor. This results in downstream signaling pathways that induce angiotensin-converting enzyme expression and endothelial dysfunction. Knockdown of GPR75 or GPCR-kinase interacting protein-1 prevented 20-HETE–mediated endothelial growth factor receptor phosphorylation and angiotensin-converting enzyme induction. In vascular smooth muscle cells, GPR75–20-HETE pairing is associated with Gαq/11 - and GPCR-kinase interacting protein-1–mediated protein kinase C–stimulated phosphorylation of MaxiKβ, linking GPR75 activation to 20-HETE–mediated vasoconstriction. GPR75 knockdown in a mouse model of 20-HETE–dependent hypertension prevented blood pressure elevation and 20-HETE–mediated increases in angiotensin-converting enzyme expression, endothelial dysfunction, smooth muscle contractility, and vascular remodeling. Conclusions: : This is the first report to identify a GPCR target for an eicosanoid of this class. The discovery of 20-HETE–GPR75 pairing presented here provides the molecular basis for the signaling and pathophysiological functions mediated by 20-HETE in hypertension and cardiovascular diseases. Abstract : Supplemental Digital Content is available in the text.